Wine prestige and experience in enhancing relationship quality and outcomes: Wine tourism in Douro. Issue 4 (20th November 2017) - Loureiro, Sandra Maria Correia; Cunha, Namércio Pereira da
Abstract : Purpose: The purpose of this study is twofold: conduct a systematic literature review on relationship quality; and analyse the effect of wine brand prestige and wine consumer experience on consumer satisfaction, as well as the wine brand image and word of mouth as outcomes. Design/methodology/approach: The authors employed a systematic approach to develop the literature review and a survey was designed and used to collect responses from 479 wine consumers and tourists. Partial Least Squares approach was used to test the proposed model and analyse the findings. Findings: The systematic approach allows to determine the core constructs of relationship quality, main antecedents and outcomes, which help in the conceptualisation of the proposed model. The findings of the survey suggest that wine brand prestige is more effective in enhancing consumer satisfaction than wine consumer experience. Consumer satisfaction acts as a mediator between wine brand prestige and wine consumer experience and the outcomes, that is, wine. Originality/value: This research sheds light on a strategic and communicational development of prestigious wine brands to enhance wine image and keep wine tourists captivated.